Heterogeneous material models for finite element analysis of the human mandible bone – A systematic review - Iman Soodmand; Ann-Kristin Becker; Jan-Oliver Sass; Christopher Jabs; Maeruan Kebbach; Gesa Wanke; Michael Dau; Rainer Bader (Heliyon)
Subject-specific finite element (FE) modeling of the mandible bone has recently gained attention for its higher accuracy. A critical modeling factor is including personalized material properties from medical images especially when bone quality has to be respected. However, there is no consensus on the material model for the mandible that realistically estimates the Young's modulus of the bone. Therefore, the present study aims to review FE studies employing heterogeneous material modeling of the human mandible bone, synthesizing these models, investigating their origins, and assessing their risk of bias.A systematic review using PRISMA guidelines was conducted on publications before 1st July 2024, involving PubMed, Scopus, and Web of Science. The search string considered (a) anatomical site (b) modeling strategy, and (c) metrics of interest. Two inclusion and five exclusion criteria were defined.A review of 77 FE studies identified 12 distinct heterogeneous material models, built based on different in vitro or computational methodologies leading to varied performance and highly deviated range of estimated Young's modulus. They are proposed for bones from five different anatomical sites than mandible and for both trabecular and cortical bone domains. The original studies were characterized with a low to medium risk of bias.This review assessed the current state of material modeling for subject-specific FE models in the craniomaxillofacial field. Recommendations are provided to support researchers in selecting density-modulus relationships. Future research should focus on standardizing experimental protocols, validating models through combined simulation and experimental approaches, and investigating the anisotropic behaviour of the mandible bone.